Ahlbergia maoweiweii sp. n. from Shaanxi, China with revisional notes on similar species (Lepidoptera: Lycaenidae) - Huang, Hao; Zhu, Jian-Qing (Zootaxa, 2016)
Ahlbergia maoweiweii sp. n. (Theclinae: Eumaeini) is described from Shaanxi, China. Ahlbergia frivaldszkyi, A. frivaldszkyi tricaudata, A. leei, A. confusa, A. ferrea and A. inopinata are reviewed. A. tricaudata stat. rev. (= A. frivaldszkyi tricaudata) is recognized as a separate species with A. tricaudata confusa stat. n. (= A. confusa) treated as its subspecies. Cornuti morphology of male genitalia is found to be diagnostic in taxonomy of the genus Ahlbergia. Other elfin butterflies externally similar to the new species are also discussed. New distributional data are given for A. clarolinea and A. chalcidis. Color photos of the type specimens of A. caesius and Novosatsuma magnapurpurea are given and a checklist of the Palaearctic elfin butterflies is updated.